Optimization of critical parameters for immobilization of Streptomyces clavuligerus on alginate gel matrix for cephamycin C production - DEVI, S; SRIDHAR, P (World journal of microbiology & biotechnology, 1999)
The optimum critical parameters for immobilization of Streptomyces clavuligerus on alginate gel matrix for cephamycin C production, i.e. sodium alginate (wt. %), CaCl sub(2) (M) and cell concentration (wt. %), curing time (h), for enhanced gel stability, were obtained employing a full factorial search. The results indicate that the concentrations of CaCl sub(2) and inoculum size were found to have a pronounced effect on cephamycin C fermentation. On the other hand, the higher concentration of sodium alginate exerted an adverse influence either individually or in combination with other variables. The path steepest ascent method has been used to optimize the variables. The optimum concentrations of matrix components were 3.218% sodium alginate, 0.996 M CaCl sub(2), 19.06% cell concentration and 17.16 h. of curing time supported higher cephamycin C production, at 48 h. of fermentation.